Epidemiology, Detection and Management of Cancer: An Overview - Mohd Hafiz, Arzmi; Anwar P. P., Abdul Majeed; Rabiu Muazu, Musa; Mohd Azraai, Mohd Razman; Hong-Seng, Gan; Ismail, Mohd Khairuddin; Ahmad Fakhri, Ab. Nasir (Springer, 2023)
Worldwide, breast cancer is recorded as the most prevalent cancer, with high mortality and morbidity rate of incidence amongst females. Meanwhile, lung cancer incidence, which is dominantly in the male population, was ranked as the third most common cancer in women. In addition, oral cancer, which refers to the cancers of the lip and oral cavity that include the lips, tongue, mouth, floor and palate, collectively had 90% of oral cancers begin as oral squamous cell carcinomas. In addition, skin cancer caused by the mutation of the skin cell has been ranked the seventeenth most common cancer worldwide, with new cases of non-melanoma skin cancer reported at 324,637. Even though many interventions have been done, the cases remain high worldwide due to late detection and poor management of the cancers. This chapter describes the epidemiology of cancers and the current method of detection and management of the diseases.